2008
DOI: 10.1016/s0140-6736(08)60419-5
|View full text |Cite
|
Sign up to set email alerts
|

Mumps

Abstract: Mumps is a common childhood infection caused by the mumps virus. The hallmark of infection is swelling of the parotid gland. Aseptic meningitis and encephalitis are common complications of mumps together with orchitis and oophoritis, which can arise in adult men and women, respectively; other complications include deafness and pancreatitis. Clinical diagnosis can be based on the classic parotid swelling; however, this feature is not present in all cases of mumps and can also occur in various other disorders. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
402
1
43

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 496 publications
(457 citation statements)
references
References 150 publications
11
402
1
43
Order By: Relevance
“…1 It has been shown that the incidence of mumps is influenced by the level of temperature and humidity. 14,20 Increases in temperature and humidity improve the duration of virus survival and virulence in the environment, 8,14 which consequently increases the opportunities for hosts to become infected with mumps. 21,22 In this study, the occurrence of mump virus infection began to increase at 20 C and began to decline if the temperatures were higher than approximately 25 C, producing an inverted V-shaped relationship.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 It has been shown that the incidence of mumps is influenced by the level of temperature and humidity. 14,20 Increases in temperature and humidity improve the duration of virus survival and virulence in the environment, 8,14 which consequently increases the opportunities for hosts to become infected with mumps. 21,22 In this study, the occurrence of mump virus infection began to increase at 20 C and began to decline if the temperatures were higher than approximately 25 C, producing an inverted V-shaped relationship.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Up to 42% of patients with mumps suffer from at least one of the following complications: orchitis, oophoritis, aseptic meningitis, encephalitis, pancreatitis, and deafness. [5][6][7][8] Similar to many infectious diseases, the number of reported mump cases exhibits a seasonal variation that has been well recognized in various countries. For example, a distinct seasonal variation was detected in the USA, with a peak occurring in April.…”
Section: Introductionmentioning
confidence: 99%
“…Complications include orchitis (post-pubertal), meningoencephalitis, oophoritis, pancreatitis, sensorineural deafness, nephritis, arthritis, thyroiditis, myocarditis and rarely death. 1,2 The measles, mumps and rubella (MMR) vaccine was introduced into many national immunization programs in the 1970s-80s; with adequate vaccination coverage, mumps incidence declined considerably. Subsequent implementation of a 2-dose schedule aimed to cover primary failure, provide boosting and improve coverage.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent implementation of a 2-dose schedule aimed to cover primary failure, provide boosting and improve coverage. [1][2][3][4] In Israel, the mumps vaccine was introduced into the schedule in 1984 and halted in 1985. In December 1988, the MMR vaccine was instituted at 15 months.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of large diagnostic datasets including saliva and urine specimens from twice MMR vaccinated mumps patients shows that high salivary viral loads at day of onset of disease is positively associated with mumps virus shedding in urine and with the occurrence of bilateral parotitis and orchitis. 30,31 The dissemination of mumps virus needs further study, as the virus has only been sporadically detected in blood during infection. 11,27,32 It has been suggested that mumps virus targets T cells, because the virus has a high affinity for T cells and efficiently replicates in these cells.…”
mentioning
confidence: 99%